FINANCIAL DUE DILIGENCE IN MERGERS AND ACQUISITIONS TRANSACTIONS (INNOVATIVE ECONOMY, 2024)
Honcharenko O.E. FINANCIAL DUE DILIGENCE IN MERGERS AND ACQUISITIONS TRANSACTIONSPurpose. The purpose of the article is to distinguish between existing approaches to differentiating the concepts of financial due diligence and auditing; improving methodological approaches to company analysis within the pre-investment stage based on systematizing possible adjustments to financial indicators.Methodology of research. To achieve the goal of the research, the following research methods were used: theoretical synthesis, analysis; interpretations and comparisons – to determine the impact of adjustments on indicators; tabular – for a visual representation of the results of adjustments.Findings. Key characteristics distinguishing the concepts of financial due diligence and auditing have been highlighted, with a focus on the concept of materiality. Systematized and provided examples of possible adjustments to financial indicators during financial due diligence in the pre-investment stage of merger and acquisition deals. Calculated adjusted indicators for a Ukrainian agricultural company based on publicly available information.Originality. Methodological approaches to business analysis in the pre-investment stage of the merger and acquisition process have been further developed, particularly in terms of systematizing potential adjustments to financial indicators within financial due diligence. The results of previous research have been systematized, and the list of characteristics suitable for analyzing the concepts of financial due diligence and auditing has been expanded, with a specific focus on the concept of materiality.Practical value. The proposed research findings contribute valuable insights to existing scientific works regarding the definition of financial due diligence and auditing, particularly in terms of their differentiation, as well as key aspects to consider in the financial analysis of potential investment targets at the pre-investment stage of the merger and acquisition process. The results of the study can be utilized to enhance transaction efficiency by improving analytical approaches and deepening the understanding of the merger and acquisition process among participants.Key words: merger and acquisition, financial due diligence, information asymmetry.
Keywords: merger and acquisition; financial due diligence; information asymmetry.